2001
DOI: 10.1002/path.989
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral mechanisms of osteoclast formation and bone resorption in Gorham–Stout disease

Abstract: Gorham-Stout disease (GSD) is a rare, massively osteolytic condition which is associated with increased vascularity and an increase in osteoclast numbers. To determine the cellular and humoral mechanisms underlying the increase in osteoclast numbers and osteolysis in GSD, this study analysed circulating osteoclast precursor numbers and sensitivity to osteoclastogenic factors in a GSD patient and age/sex-matched controls. Monocytes were cultured with M-CSF (25 ng/ml) and RANKL (30 ng/ml) and osteoclast formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 19 publications
4
95
0
9
Order By: Relevance
“…In our case series, the osteoclast in areas of bone resorption was found in only five cases (7.5%), which suggested "osteoclastosis" may be not necessary in this entity. Some authors described that interleukin-6 (IL-6) may cause bone resorption because it can stimulate osteoclast activity and increase sensitivity of osteoclast precursors to humoral factors (Möller et al, 1999;Hirayama et al, 2001;Hammer et al, 2005). Devlin et al (1996) demonstrated that the blood level of IL-6 was seven times the upper limit of the normal range, and fell to one quarter the pretreatment value after further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, the osteoclast in areas of bone resorption was found in only five cases (7.5%), which suggested "osteoclastosis" may be not necessary in this entity. Some authors described that interleukin-6 (IL-6) may cause bone resorption because it can stimulate osteoclast activity and increase sensitivity of osteoclast precursors to humoral factors (Möller et al, 1999;Hirayama et al, 2001;Hammer et al, 2005). Devlin et al (1996) demonstrated that the blood level of IL-6 was seven times the upper limit of the normal range, and fell to one quarter the pretreatment value after further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hirayama and colleagues 130 have reported on the cellular and humoral mechanisms of osteoclast formation and bone resorption in patients with Gorham-Stout syndrome. These authors suggested that the increase in osteoclast formation in Gorham-Stout syndrome is not due to an increase in the number of circulating osteoclast precursors, but rather to an increase in the sensitivity of these precursors to humoral factors which promote osteoclast formation and bone resorption.…”
Section: Etiopathologymentioning
confidence: 99%
“…Мнения о роли остеокластов в деструкции костной ткани при GSD противоречивы: ряд исследователей подтверждает их высокую активность [1,5,6,18,22,26,32,36,42,44,48,50], другие отмечают их отсутствие в оча-гах остеолиза [12,13,21,45,51]. При-чина такого противоречия, возмож-но, обусловлена проведением гисто-логического исследования на разных стадиях процесса [4].…”
Section: рисunclassified